Temporal changes of abundance, biomass and production of copepod community in a shallow temperate estuary (Ria de Aveiro, Portugal) - Leandro, S. M.
The present study reports on temporal changes of abundance, biomass and secondary production of the copepod community of Ria de Aveiro (Portugal). Zooplankton sampling and hydrological measurements (salinity, temperature, chlorophyll a and nutrients concentrations) were conducted at four occasions (June 2000, September 2000, December 2000 and March 2001), at 6 sampling stations and during ebb and flood. The contribution of copepods (from nauplius to adults) to the total abundance and biomass of the zooplankton community of Ria de Aveiro (Portugal) was equal to 63.6% and 62.0%, respectively (annual average). The estimate of nauplius abundance given by two zooplankton nets with different meshes was significantly different (P < 0.001) with the 64 μm net collecting 13.9 times more than the 125 μm one. No significant differences were found for copepodites and adults. The abundance of all development stages (except adults) was positively correlated (P < 0.05) with salinity and temperature. The seasonal patterns of abundance and biomass were similar to those found in other temperate coastal waters. Mean daily secondary production rate (mean ± SE) estimated by the Huntley and Lopez growth model [Huntley, M.E., Lopez, M.D.G., 1992. Temperature-dependent production of marine copepods: a global synthesis. American Naturalist 140, 201–242] was 22% higher than the value given by the application of the Hirst and Bunker model [Hirst, A.G., Bunker, A.J., 2003. Growth of marine planktonic copepods: global rates and patterns in relation to chlorophyll a, temperature, and body weight. Limnology and Oceanography 48, 1988–2010]: 3.71 ± 0.540 and 2.90 ± 0.422 mg C m−3 d−1, respectively.